2018
DOI: 10.1007/s11116-018-9957-5
|View full text |Cite
|
Sign up to set email alerts
|

A modeling approach for matching ridesharing trips within macroscopic travel demand models

Abstract: State of the art travel demand models for urban areas typically distinguish four or five main modes: walking, cycling, public transport and car. The mode car can be further split into car-driver and car-passenger. As the importance of ridesharing may increase in the coming years, ridesharing should be addressed as an additional sub or main mode in travel demand modeling. This requires an algorithm for matching the trips of suppliers (typically car drivers) and demanders (travelers of non-car modes). The paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…A similar study sponsored by Ruter, the Oslo region's public transport company, focused on the impact of autonomous cars in Oslo [32]. A second grouping of studies were identified that focused on applying new approaches to model shared mobility at the city level, represented by Ann Arbor, Babcock Ranch, Manhattan [33], Zurich [34,35], and Stuttgart [36].…”
Section: Review Of City-level Maas Studiesmentioning
confidence: 99%
“…A similar study sponsored by Ruter, the Oslo region's public transport company, focused on the impact of autonomous cars in Oslo [32]. A second grouping of studies were identified that focused on applying new approaches to model shared mobility at the city level, represented by Ann Arbor, Babcock Ranch, Manhattan [33], Zurich [34,35], and Stuttgart [36].…”
Section: Review Of City-level Maas Studiesmentioning
confidence: 99%
“…Besides, another key characteristic influencing the intricacy of rider-vehicle matching is the number of trip segments (Friedrich et al, 2018). Specifically, the potential matches for a customer request rise with the number of segments, thereby increasing the computational time for enumerating all the combinations.…”
Section: Ride-matchingmentioning
confidence: 99%
“…M. Friedrich, M. Hartl, C. Magg represent the static and dynamic modes of working with a car, separating the carpooling mode into several types, such as one to one, one to many, and many to many, and developed the path choosing method and speed optimization model, was investigated [6].…”
Section: Problem Analysis and The Goal Of Researchmentioning
confidence: 99%